Neuropathological correlate of the "concentric target sign" in MRI of HIV‐associated cerebral toxoplasmosis. Issue 2 (25th February 2013) - Mahadevan, Anita; Ramalingaiah, Arvinda Hanumantapura; Parthasarathy, Satishchandra; Nath, Avindra; Ranga, Udaykumar; Krishna, Shankar Susarla
<x xml:space="preserve">Abstract</x> Cerebral toxoplasmosis is a frequent cause of focal brain lesions in the setting of immunodeficiency states, particularly acquired immune deficiency syndrome (AIDS), and magnetic resonance imaging (MRI) is an important diagnostic modality to differentiate toxoplasmosis from tuberculoma, and primary central nervous system lymphoma with diverse therapeutic implications. Several imaging patterns have been described in cerebral toxoplasmosis. The "concentric target sign" is a recently described MRI sign on T2‐weighted imaging of cerebral toxoplasmosis that has concentric alternating zones of hypo‐ and hyperintensities. It is believed to be more specific than the well‐known "eccentric target sign" in the diagnosis of cerebral toxoplasmosis and hence more useful in differentiation from other focal brain lesions in the context of AIDS. The concentric target sign, seen in deep parenchymal lesions, is distinct from the surface‐based cortical "eccentric" target sign. The histopathological correlate of the latter has been recently described, but that of the concentric target sign is not known. In this study we describe the neuropathological correlate of this concentric target sign from the postmortem of a 40‐year‐old man with AIDS‐associated cerebral toxoplasmosis. The concentric alternating zones of hypo/hyper/iso/intensities corresponded to zones of hemorrhage/fibrin‐rich necrosis with edema/coagulative compact necrosis/inflammation with foamy histiocytes admixed with hemorrhage forming the outermost zone, respectively. The exclusive specificity of this sign in cerebral toxoplasmosis remains to be further elucidated. J. Magn. Reson. Imaging 2013;38:488–495. © 2013 Wiley Periodicals, Inc.